Fabrication and characterization of Pickering emulsion gels stabilized by zein/pullulan complex colloidal particles. (22nd December 2020) - Liu, Qian; Chang, Xia; Shan, Yang; Fu, Fuhua; Ding, Shenghua
Abstract: BACKGROUND: Zein particles are unsuitable as stabilizers of Pickering emulsions because of their high hydrophobicity. However, few studies have reported on the use of a strong hydrophilic neutral polysaccharide to regulate its wettability. In this work, zein/pullulan complex particles (ZPPs) were formulated by an anti‐solvent method to fabricate Pickering emulsions. RESULTS: The presence of pullulan increased the size, decreased the zeta, and provided excellent resistance to the gravitational separation of zein. Scanning electron microscopy (SEM) revealed that the shape of zein particles changed from spherical as they became aggregated ZPP nanoparticles. Fourier transform infrared (FTIR) spectroscopy indicated that the flocculation phenomenon of ZPPs was related to the hydrogen bond between zein and pullulan. Moreover, the hydrophobicity of zein was modified by hydrophilic pullulan to endow the ZPPs with nearly neutral wettability when the mass ratio was 15:1, allowing for the preparation of stable Pickering emulsions. In contrast to zein, the ZPPs contributed to building a compact interface layer around the droplets and smaller emulsion droplets. Under a certain ZPP concentration, the size and viscosity of emulsion increased with an increase in the oil volume fraction, indicating that the Pickering emulsions stabilized by ZPPs showed better stability against coalescence. Confocal laser scanning microscopy (CLSM) revealed that the ZPPs constructed a dense filling layer on the surface of oil droplets, thus further emphasizing that ZPPs can potentially be used in fabricating Pickering emulsion gels. CONCLUSION: Zein/pullulan complex particles are an excellent Pickering emulsion gel stabilizer that can be used in the delivery system of bioactive substances in food formulations. © 2020 Society of Chemical Industry